INTERCULTURAL COMMUNICATION IN THE CONTEXT OF GLOBALIZATION (Ustozlar uchun, 2026)
Intercultural communication has become one of the most significant areas of study in modern linguistics, sociology, and education due to the rapid processes of globalization, migration, and international cooperation, which have brought people from diverse cultural backgrounds into constant interaction. This article aims to analyze the concept of intercultural communication, its theoretical foundations, practical importance, and major challenges, while also emphasizing the role of intercultural communicative competence in fostering mutual understanding and effective interaction among representatives of different cultures. Special attention is given to linguistic and non-linguistic factors influencing communication, as well as to the necessity of developing intercultural awareness in educational and professional contexts.